Microstructural Optimization Approach of Solar Cell Interconnectors Fatigue Behavior for Enhanced Module Lifetime in Extreme Climates. (August 2016) - Meier, Rico; Pander, Matthias; Großer, Stephan; Dietrich, Sascha
Abstract: Fatigue of the cell interconnectors is one of the main reasons for module failure. Especially with respect to module application in extreme climates new demands on solar cell interconnectors will arise. Optimizations in the manufacturing process to generate a product demand related microstructure are a key to improve the material behavior of interconnectors with respect to extreme climate loading conditions without increasing costs. For achieving this goal several aspects were considered in this paper: Influence of the annealing process on the fatigue behavior: Due to an optimization of the annealing process an increase in ribbon fatigue strength by a factor of four could be achieved. The effect consists of two parts: Firstly, annealing influences the geometrical shape generated during the fatigue experiment. Secondly, it affects crack formation and crack growth during fatigue. Influence of temperature on fatigue behavior: an increase in temperature leads to a significant reduction in fatigue strength (from 25 to 100 °C by factor 3). This results from increased dislocation creep at higher temperatures. Microstructural comparison of fracture patterns: The loading amplitude determines the roughness of the fracture surface: Smaller amplitudes lead to a coarser surface structure. This is important to compare accelerated lifetime testing in the lab and modules failures from the field. Simulation of temperature and microstructure dependent fatigue for lifetime prediction: Exemplarily it will be depicted how optimized fatigue behavior in the lab translates into real module lifetime under extreme climate conditions. Despite the actual numbers which show the potential of the approach, but could vary from sample to sample, the focus of the paper is the method itself and its physical background.